A single-center, randomized, open-label, two-period, crossover, fasted bioequivalence study: comparing recombinant human follicle-stimulating hormone for injection (JZB30) with Gonal-f® in healthy Chinese female participants - Chen, Zhuo; Yu, Qin; Feng, Shiyin; Mo, Li; Cai, Linrui; Du, Chunfeng; Du, Dan; Zou, Qin (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the pharmacokinetic (PK) bioequivalence, safety, and immunogenicity of recombinant human follicle-stimulating hormone (rhFSH) for injection (code name: JZB30), developed by Chengdu Jingze Biopharmaceutical Co., Ltd., in comparison with Gonal-f® developed by Merck Serono in healthy adult Chinese female participants.Methodssingle-center, randomized, open-label, two-period crossover study for bioequivalence assessment enrolled 48 healthy adult female participants, who were equally and randomly assigned to two treatment sequences. Each participant received a single subcutaneous injection of either JZB30 or Gonal-f® at a dose of 225 IU on Day 1 and again on Day 11 as part of the crossover design. Blood concentrations of FSH were measured using a validated electrochemiluminescence immunoassay, followed by non-compartmental PK analysis. Safety and immunogenicity were systematically monitored throughout the study period, including adverse events and anti-FSH antibody testing.ResultsThe geometric mean ratios (GMRs) of the primary PK parameters—Cmax, AUC0-t, and AUC0−∞–after baseline correction were 106.12%, 108.04%, and 115.32%, respectively. The 90% confidence intervals for these parameters (Cmax:101.92%–110.49%; AUC0-t:104.13%–112.09%; AUC0−∞,: 106.47%–124.90%) all fell within the predefined bioequivalence range of 80%–125%. All adverse events (AEs) were mild (Grade 1) and resolved spontaneously without requiring medical intervention. One participant tested positive for anti-FSH antibodies following administration of the reference formulation; however, the antibody response reverted to negative without any intervention, indicating a low risk of immunogenicity.ConclusionJZB30 was demonstrated to be pharmacokinetically bioequivalent to Gonal-f® in healthy adult Chinese female participants, with comparable safety profiles and a low risk of immunogenicity. These findings provide evidence to support the clinical application of JZB30 as a biosimilar to Gonal-f®.Clinical Trial RegistrationThe trial was registered on ClinicalTrials.gov under identifier NCT06778304.